Institutional approach to global corporate governance business systems and beyond - Dow, Sandra; Choi, Jongmoo Jay, 1945- (International finance review ;, 2008)
This edited volume contains original papers examining issues concerning the effects of national and international institutional factors on corporate governance and performance. This volume stresses the relevance of national business systems (including culture, law and politics) alongside industrial and institutional infrastructure to assess the efficacy of corporate governance regimes. Modern governance research redefines the boundaries of the firm to include a wider group of stakeholders beyond stockholders. Newer research indicates that national context is the over-riding element in understanding corporate governance regulation and outcome. In the Anglo-Saxon world, corporate governance is designed to reduce the conflict of interest that exists between owners and managers occasioned by the separation of ownership and control. The divergence in national business systems has led scholars to question whether the rush to adopt US-style regulation internationally is appropriate. The papers in this volume highlight aspects of institutional context in different countries, ranging from traditional corporate governance mechanisms at the firm level, to issues affecting the country level quality of corporate governance, including culture and the role of elites.